2007
DOI: 10.1111/j.1469-8986.2007.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Chest pain is inversely associated with blood pressure during exercise among individuals being assessed for coronary heart disease

Abstract: Acute and chronic increases in blood pressure have been related to decreases in pain perception. This phenomenon has been studied primarily using acute experimental pain stimuli. To extend the literature to naturalistic pain and in particular the problem of silent cardiac ischemia, this study examined the relationship between blood pressure and chest pain during exercise stress testing. Nine hundred seven (425 men, 482 women) individuals undergoing exercise stress testing for diagnosis of possible myocardial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Hagen et al (2005) documented a 10-60% lower prevalence of chronic musculoskeletal complaints in individuals with essential hypertension, as well as an inverse linear relationship between blood pressure and occurrence of such symptoms. In persons being assessed for coronary heart disease, chest pain experienced during treadmill exercise was inversely associated with blood pressure (Ditto et al, 2007). In persons being assessed for coronary heart disease, chest pain experienced during treadmill exercise was inversely associated with blood pressure (Ditto et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hagen et al (2005) documented a 10-60% lower prevalence of chronic musculoskeletal complaints in individuals with essential hypertension, as well as an inverse linear relationship between blood pressure and occurrence of such symptoms. In persons being assessed for coronary heart disease, chest pain experienced during treadmill exercise was inversely associated with blood pressure (Ditto et al, 2007). In persons being assessed for coronary heart disease, chest pain experienced during treadmill exercise was inversely associated with blood pressure (Ditto et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…A longitudinal study revealed a 30% lower risk of development of non-migraine headache across an 11 years follow-up interval in hypertension (Hagen et al, 2002). In persons being assessed for coronary heart disease, chest pain experienced during treadmill exercise was inversely associated with blood pressure (Ditto et al, 2007). In patients recovering Table 2 Regression analyses for the prediction of pain experience from systolic blood pressure, dp/dt and baroreflex sensitivity (Beta and R-values, significance levels of Beta * for p < .05, ** for p < .01) Systolic blood pressure dp from prostatectomy, the degree of postsurgical pain was found to correlate negatively with blood pressure (France and Katz, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Baroreceptor‐related inhibition is among the most important factors mediating the well‐known connection between tonic blood pressure and pain sensitivity (Zamir & Shuber, ). While hyperalgesia has been demonstrated in individuals with chronically low blood pressure (Duschek, Dietel et al., ; Duschek, Schwarzkopf, & Schandry, ), lower sensitivity to experimental pain as well as reduced proneness to clinical pain complaints occur in hypertension (Ditto, D'Antono, & Dupuis, ; Ghione, ; Hagen et al., ).…”
Section: Baroreflex Function and Pain Perceptionmentioning
confidence: 99%
“…Interactions between cardiovascular states, especially blood pressure (BP) and central nervous function, are well known. High levels of BP, for instance, have been associated with reduced sensitivity to experimentally induced pain (Bruehl et al., ; Myers et al., ), and clinical pain is somewhat less prevalent in persons suffering from hypertension (Hagen et al., , ; Ditto et al., ). In contrast, individuals with chronically low BP tend display an exaggerated nociceptive response (Duschek et al., , ).…”
Section: Introductionmentioning
confidence: 99%